7 Diffusion tensor cardiovascular magnetic resonance in cardiac amyloidosis. (March 2019) - Khalique, Z; Ferreira, PF; Scott, AD; Nielles-Vallespin, S; Wage, R; Martinez-Naharro, A; Fontana, M; Hawkins, PN; Firmin, DN; Pennell, DJ
Abstract : Introduction: Cardiac amyloidosis is a disease of infiltration, typically by light chains (AL) or transthyretin (ATTR). We studied cardiac amyloidosis using diffusion tensor cardiovascular magnetic resonance (DT-CMR), which is the only non-invasive tool able to assess cardiac microstructure in-vivo . Methods and results: Biphasic STEAM DT-CMR was successfully performed in 20 cardiac amyloidosis patients (10 AL, 10 ATTR) and 10 age and sex matched controls. Compared with controls, amyloid patients had higher mean diffusivity (MD); median [IQR] 1.46 [1.36–1.54] × 10 −3 mm 2 /s vs 1.15 [1.03–1.20] × 10 −3 mm 2 /s (p<0.001), shown in figure 1A . MD correlated with T1 (R 2 =0.76, p<0.001) and extracellular volume (ECV) (R 2 =0.47, p=0.004). Amyloid patients had lower fractional anisotropy (FA) compared to controls; 0.43 [0.39–0.45] vs (0.55 [0.52–0.60], p<0.001), as shown in figure 1B . FA inversely correlated with T1 (R 2 =0.59, p<0.001). Amyloid patients had elevated diastolic E2A and reduced E2A mobility (both <0.001). Segmental analysis for co-location of FA and MD with ECV amyloid infiltration showed good correlation (both p<0.001). Example maps are shown in figure 2 . There was no significant difference in MD, FA or E2A mobility between amyloid subtypes. Conclusion: In cardiac amyloidosis, DT-CMR characterises the microstructural effects of infiltration, and increases in MD show good correlation with increases in ECV. The novel insights from DT-CMR offer a deeper understanding of pathophysiological mechanisms in cardiac amyloidosis. With further development, DT-0CMR might offer a gadolinium free assessment of amyloid burden, which is of particular value in renal failure.